Pengenalan Dasar Game Development Dengan Scratch: Upaya Peningkatan Kompetensi Digital Siswa SMA PGRI 22 Serpong - Muhammad Daffa; Achmad Anta Maulana; Adi Ranlam Hidayat; Aril Saputra; Dimas Agung; Fawwaz Rafian Syafiq; Muhammad Liong Ghozaly; Rizki Khairul Anwar; Rizki Ramadhani; Solahudin; Tri Prasetyo (AMMA : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to enhance digital literacy of SMA PGRI 22 Serpong students through game development training using Scratch platform. The implementation method consisted of three stages: (1) introduction to Scratch interface, (2) hands-on practice in creating simple games, and (3) project presentation. Evaluation results showed 100% of participants (20 students) successfully created their first game prototypes within 3 hours of training. This activity not only improved understanding of basic programming concepts by 40% (based on pre-test and post-test) but also fostered students' interest in creative technology fields. The outputs including training modules, 20 simple game projects, and this publication article are expected to become a digital learning model for schools.